Role of attractive forces in determining the equilibrium structure and dynamics of simple liquids - Toxvaerd, S. (Condensed Matter Physics, 2015)
Molecular Dynamics simulations of a Lennard-Jones system with different range of attraction show that the attractive forces modify the radial distribution of the particles. For condensed liquids only, the forces within the the first coordination shell (FCS) are important, but for gases and moderate condensed fluids, even the attractive forces outside the FCS play a role. The changes in the distribution caused by neglecting the attractive forces, lead to a too high pressure. The weak long-range attractions damp the dynamics and the diffusion of the particles in gas-, super critical fluid- and in liquid states. The values of self-diffusion coefficients (SDC) agree qualitatively with a modified Cohen-Turnbull model. The SDC-s along the critical isotherm show no anomaly at the critical point in agreement with experimental data.